Critical Teacher Talk: Successful English for Academic Purposes Classroom Practices in a Global Campus - Kim, Namsook (Journal of International Students, 2016)
Drawn on the sociocultural paradigm, I examined teacher-student communication with emphasis on teacher’s talk and its role on international students’ learning English as a Second Language in an English for Academic Purposes classroom in a global campus in the U.S. Developmental data analyses of class observations, teacher and student interviews, and documents led to finding multidimensional characteristics of Critical Teacher Talk (CTT). I also found evidence of the role of CTT on production-process-affective aspects of learning English as an International Language. The findings further shed insights on the need to train and practice Critical International Language Pedagogy with the triadic principles—transnational culture building, critical caring, and authentic learning—among international higher education educators and teachereducators.